Islamic Law Reform in Indonesia from the Perspective of Maqāṣid Al-Sharī'ah: Kerinci’s Intellectual Views (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Benefits cannot be achieved without going through reform, namely efforts to apply the law to the reality of society. So, reform is a necessity, although these steps do not mean replacing the teachings and laws that are absolute, fundamental, and universal and have been stated in authentic provisions. Reformation has quite wide room for movement in renewing ways of understanding, interpreting, reformulating, and conducting studies of Islamic law that are outside the area of Qath'iyyah, namely the provisions of Zhanniyyah, which are included in the scope of the area of reform. This research is included in the empirical legal method, which is explained by an analysis of the theory of maqāṣid al-sharī'ah according to intellectuals in Kerinci. This method provides an explanation of Islamic law that can be applied in the current era through renewal with maqāṣid al-sharī'ah analysis. Data was collected through in-depth interviews and a literature study. This study concludes that the renewal of Islamic law from the perspective of maqāṣid al-sharī'ah has three ways: first, prioritizing the worship aspect; second,  the muamalah aspect; and third, a combination of both. The third method is a combination of ways of knowing maqāṣid al-sharī'ah through a pronunciation approach and a meaning approach. Utility, as the content of Islamic law, which is systematized through maqāṣid al-sharī'ah analysis, is of course not only seen in technical articles but must also be seen as something that contains philosophical values so that it becomes a universal and dynamic identity. According to Islamic intellectuals in Kerinci, the compilation of Islamic law has urgency and relevance to maqāṣid al-sharī'ah and is still very much needed as a step to reform Islamic law in Indonesia.
Keywords: Reform of Islamic law; maqāṣid al-sharī'ah; compilation of Islamic law